Contact Lens Visual Rehabilitation in Keratoconus and Corneal Keratoplasty. (15th January 2012) - Ozkurt, Yelda; Atakan, Mehmet; Gencaga, Tugba; Akkaya, Sezen
Abstract : Keratoconus is the most common corneal distrophy. It's a noninflammatory progressive thinning process that leads to conical ectasia of the cornea, causing high myopia and astigmatism. Many treatment choices include spectacle correction and contact lens wear, collagen cross linking, intracorneal ring segments implantation and finally keratoplasty. Contact lenses are commonly used to reduce astigmatism and increase vision. There are various types of lenses are available. We reviewed soft contact lenses, rigid gas permeable contact lenses, piggyback contact lenses, hybrid contact lenses and scleral-semiscleral contact lenses in keratoconus management. The surgical option is keratoplasty, but even after sutur removal, high astigmatism may stil exists. Therefore, contact lens is an adequate treatment option to correct astigmatism after keratoplasty.